Identification of Arbuscular Mycorrhazal Fungi on Chili Pepper Plants (Capsicum Frutescens) in Sarilamak Village, Harau District - Hawari, Hawari; Yefriwati, Yefriwati; Darmansyah, Darmansyah; Ramadhano, Agung (ITScience (Information Technology and Science), 2025)
Chili pepper (Capsicum Frutescens) is one of the horticultural commodities that is in great demand and has economic value. The nutritional content of chili peppers includes fat, protein, carbohydrates, calcium, iron, phosphorus, vitamins A, B1, B2, C, and alkaloid compounds, namely flavonoids, capsaicin, oleoresin, and essential oils. Chili pepper production in Lima Puluh Kota Regency has decreased in the last five years; one of the causes is the continuous use of inorganic fertilizers. One technology that can improve soil quality and is also environmentally friendly is the use of biofertilizers, one of which is Arbuscular Mycorrhizal Fungi (AMF). AMF are soil microorganisms that help in the nutrient cycle, the existence of mutualistic symbiosis between fungi and the roots of higher plants. However, the use of AMF in chili pepper plants, especially in Sarilamak Village, Harau District, has not been carried out, so research on the identification of AMF spores in chili pepper plants in Sarilamak Village is necessary. This research is the first identification of AMF diversity in Sarilamak Village. Soil samples were taken and observed descriptively and presented in tables and figures. The types of AMF spores found were Acaulospora sp, Glomus sp, Gigaspora sp, and Scutellospora sp. The most common type of AMF found was Acaulospora sp with 101 spores and the least was Scutellospora sp with 11 spores. Acaulospora sp spores showed potential inoculum intended for cayenne pepper cultivation in Sarilamak.